The contribution of learning outcomes, creativity, and emotional intelligence to students' entrepreneurial interest - Angela Yosiana; Rahmiati Rahmiati; Yuliana Yuliana; M. Giatman (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aims to analyze the contribution of learning outcomes in Creative Product and Entrepreneurship, creativity, and emotional intelligence to the entrepreneurial interest of XII grade students at SMKS Korpri Duri. This research employed a quantitative approach using multiple linear regression analysis to examine the contribution of each independent variable to the dependent variable. The population consisted of 127 students, with a sample of 97 selected through purposive sampling. The research instrument was a closed-ended questionnaire using a Likert scale, which had been tested for validity and reliability. The analysis results show that the three independent variables learning outcomes, creativity, and emotional intelligence simultaneously have a significant effect on entrepreneurial interest, with an F-value of 28.836 and significance level of 0.000. Partially, learning outcomes (B = 0.265; sig. 0.000), creativity (B = 0.367; sig. 0.000), and emotional intelligence (B = 0.170; sig. 0.000) each have a positive and significant influence on entrepreneurial interest. The R Square value of 0.592 indicates that these three independent variables contribute 59.2% to students' entrepreneurial interest. Thus, it can be concluded that learning outcomes, creativity, and emotional intelligence are key factors in fostering entrepreneurial interest among vocational school students.